The Impact of Implementing Connector Applications on Tax Business Processes in Indonesia - Buana Handoko, Rangga Restu; Ritchi, Hamzah; Adrianto, Zaldy (Dinasti Publisher, 2025)
This study aims to analyze the effect of implementing a technology-based Application Programming Interface (API) connector application on tax business processes in Indonesia. This study uses the Technology-Organization-Environment (TOE) and Technology Acceptance Model (TAM) theoretical approaches to evaluate technology, convenience, benefits, and confidentiality and security factors in improving the efficiency and effectiveness of tax business processes. Data were obtained from a survey of taxpayers registered at the Pratama Bandung Tax Service Office (KPP) using a descriptive quantitative method. The results of the study indicate that technology and convenience factors have a significant positive effect on tax business processes. However, the benefits and confidentiality and security factors do not show a significant effect. In addition, technology has been shown to improve transparency, accuracy, and integration of the tax system. This study recommends the development of a more intuitive application interface, improvement of due date reminder features, and education for taxpayers to increase the adoption of API-based tax technology.